2020
DOI: 10.1101/2020.11.09.375584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Label-free lymphocytes reconstitution using side scatter for optimal T cell manufacturing

Abstract: SUMMARYLymphocyte biology research commonly involves purification of lymphocyte subpopulations by fluorescence-activated cell sorting (FACS) or immunomagnetic separation (IMS), both of which typically rely on antibody labeling of validated cell markers. Methods enabling label-free segregation of lymphocyte subpopulations would be invaluable with regard to less-perturbation, simplicity and cost-effectiveness. Here, we introduce TRuST, a label-free approach for T cell reconstitution using side-scatter (SSC). TRu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
(106 reference statements)
1
1
0
Order By: Relevance
“…These IL-2 + TNF-α + or IL-2 + TNF-α + IFN-γ + had a dramatic upregulation of genes involved in IL2-STAT and TNF-NFKB signaling pathways, and genes favoring cell survival and proliferation/differentiation (e.g., CSF2, IER3, CCND3, EZH2, and Mycregulated genes). These data have extended our previous finding that the generation of TCMRA during the production of therapeutic T cells was wellcorrelated with the proportion of TN in cellular starting material 42 , and cell products containing more TCMRA were manifested by younger phenotypes and superior functions that are recognized to be good for therapeutic outcomes.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…These IL-2 + TNF-α + or IL-2 + TNF-α + IFN-γ + had a dramatic upregulation of genes involved in IL2-STAT and TNF-NFKB signaling pathways, and genes favoring cell survival and proliferation/differentiation (e.g., CSF2, IER3, CCND3, EZH2, and Mycregulated genes). These data have extended our previous finding that the generation of TCMRA during the production of therapeutic T cells was wellcorrelated with the proportion of TN in cellular starting material 42 , and cell products containing more TCMRA were manifested by younger phenotypes and superior functions that are recognized to be good for therapeutic outcomes.…”
supporting
confidence: 81%
“…Thus, we further dissected the secretion potency of heterogeneous cell 12 subpopulations, especially T lymphocytes. We found that pre-existing central memory T cells with CD45RA expression (TCMRA) (Figure S4E) 42,43 regardless of CD4 + T or CD8 + T cells had the rapidest cytokine secretion, primarily TNF-α + IL-2 + and TNF-α + within one hour post activation, while those moredifferentiated counterparts like central memory without CD45RA expression (TCMO) and effector memory (TEM and TEM_late) tended to secret mono-cytokine such as TNF-α + or IL-2 during initial stimulation (Figure 3A). CD8 + TCMRA continued to release multiple cytokines, specifically IFN-γ-involved triple or double positive cytokines, whereas amongst CD4 + T cells, CD4 + TCMRA and CD4 + TCMO_late were the multi-cytokine releasing cells (Figure 3B, C).…”
Section: Traps-seq Identifies Cell Subpopulations With Heterogeneous Secretion Potencymentioning
confidence: 95%